2000
DOI: 10.1046/j.1365-2141.2000.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma viscosity and all‐cause mortality: results from the MONICA–Augsburg Cohort Study 1984–92

Abstract: Summary. Several studies have reported a strong association between various markers of the acute-phase response and death from cardiovascular diseases and all-cause mortality. Inflammation at a low level of intensity may be a common phenomenon associated with the majority of causes of death owing to chronic diseases. We sought to investigate the association of plasma viscosity with all-cause mortality in a cohort of apparently healthy men. The study population consisted of 964 men aged 45±64 years at entry, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 36 publications
0
17
1
1
Order By: Relevance
“…In contrast to two other prospective studies (Koenig et al, 2000;Lowe et al, 2000), plasma viscosity was not associated with incident mortality. Following adjustment for evidence of baseline CVD, and for classic cardiovascular risk factors (which were associated with baseline levels of blood viscosity determinants: Lowe et al, 1988), only fibrinogen (measured as clottable fibrinogen by the von Clauss assay) was significantly associated with mortality.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In contrast to two other prospective studies (Koenig et al, 2000;Lowe et al, 2000), plasma viscosity was not associated with incident mortality. Following adjustment for evidence of baseline CVD, and for classic cardiovascular risk factors (which were associated with baseline levels of blood viscosity determinants: Lowe et al, 1988), only fibrinogen (measured as clottable fibrinogen by the von Clauss assay) was significantly associated with mortality.…”
Section: Discussioncontrasting
confidence: 51%
“…Three prospective studies (the present; and Koenig et al, 2000, andLowe et al, 2000) have now shown that measures (or determinants) of blood viscosity are associated with incident mortality. However, the results of the present study, and of another prospective study in West of Scotland men (Lowe et al, 2000), show that a major part of this association is due to the mutual associations of blood viscosity and its determinants, baseline evidence of CVD, cardiovascular risk factors and risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore plasma viscosity, in addition to intraluminal pressure and flow pattern, is a major determinant of endothelial shear stress in this particular region. Plasma viscosity is used as a marker for different diseases in humans such as coronary artery disease (Koenig et al 2000;Lowe et al 2000), lupus erythematosus (Reid & DeCeulaer, 1999;Rosenson et al 2001) and rheumatoid arthritis (Grassi et al 1998). However, an increase in plasma viscosity with the progression of disease (Hoffmeister et al 2001) or with therapy (Gibbs et al 2001) was not observed.…”
Section: Differences In Plasma Viscositymentioning
confidence: 97%
“…In addition, we prospectively analyzed the association between plasma viscosity and total mortality in the same cohort and found a RR to die of 2.68 (95 % CI, 1.63 -4.42) in subjects being in the top quintile of the plasma viscosity distribution compared to the bottom quintile [13].…”
Section: Plasma Viscositymentioning
confidence: 99%